2012
DOI: 10.1111/j.1757-7861.2011.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between anterior and posterior decompression for cervical spondylotic myelopathy: subjective evaluation and cost analysis

Abstract: Both anterior and posterior decompressions (with instrumentation) are effective procedures for improving the neurological outcomes of patients with CSM. However, although the two approaches have similar health care costs, anterior cervical corpectomy (with instrumentation) seems to be subjectively assessed by patients as better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…The finding of higher third-party payments for the treatment of patients undergoing a posterior approach is consistent with the previously reported literature. [17][18][19] Our findings are supported by those of Shamji et al, who showed that resource utilization was significantly higher for patients undergoing a posterior approach for diffuse cervical spondylosis. 23 In the current study, we did not separate fusion from nonfusion posterior procedures, which could impact the rates of reimbursement.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The finding of higher third-party payments for the treatment of patients undergoing a posterior approach is consistent with the previously reported literature. [17][18][19] Our findings are supported by those of Shamji et al, who showed that resource utilization was significantly higher for patients undergoing a posterior approach for diffuse cervical spondylosis. 23 In the current study, we did not separate fusion from nonfusion posterior procedures, which could impact the rates of reimbursement.…”
Section: Discussionsupporting
confidence: 87%
“…Each approach has specific advantages and disadvantages, and controversy remains in terms of the optimal approach for subgroups of patients. 15,16,18,19,23 A systematic review by Lawrence et al did not demonstrate any clear advantage to either the anterior or posterior surgical approach for patients with multilevel CSM. 17 The authors recommended an individualized approach for patients with CSM based on patient and disease characteristics.…”
mentioning
confidence: 96%
“…Fourteen studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26] reporting the SF36 outcomes of 1966 patients with degenerative cervical myelopathy were included, while excluding 181 studies during study selection stage (Appendix 1). Because many studies had more than 1 arm, 22 datasets were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Cervical spondylotic myelopathy (CSM) is a degenerative disorder of the cervical spine characterized by narrowing of the cervical spinal canal and compression of the spinal cord. Clinical manifestations of CSM may include symptoms such as paresthesia in the upper limbs, spastic paraparesis, impaired sensation, and gait disturbance. When cervical medullary are compressed to a certain degree, gait abnormalities such as unsteady walking and impaired balance may be observed; such abnormalities are a strong indication for surgical intervention and can be used as an index to assess postoperative recovery.…”
Section: Introductionmentioning
confidence: 99%